Influence of training and development on job satisfaction, loyalty and retention: A study among academics at a selected University of Technology - Mampuru, Motlokoe Philharmon (Vaal University of Technology, 2022)
This study has extended the research on the influence of training and development on job satisfaction, loyalty, and retention among academics at a university of technology. The Universities of Technology (UoTs) were established in South Africa with the aim of rearranging the higher education system. The introduction of these new types of universities into the higher education setup was faced with various challenges that included, but not limited to extreme competition among the institutions of higher learning. As newcomers into the higher education environment, the Universities of Technology performed poorly compared to traditional universities in terms of research and innovation activities. To be competitive in the higher education environment, UoTs had to embark on training and development of their staff. To this day, training and development interventions are common practices within UoTs. This study used a quantitative research approach and a non-probability convenience sampling technique to determine the relationships between training and development, job satisfaction, loyalty, and retention among academics. Out of 350 hand-delivered questionnaires, 270 were completed and returned by the participants. A pilot study and pre-testing of the questionnaire were undertaken prior the main study to ensure reliability of the scales. The collected data were analysed through descriptive statistics, correlation analysis, and regression analysis using Statistical Packages for Social Sciences (SPSS) version 26. The relationships between the study’s constructs were determined through correlation and regression analyses. All the results of correlational combinations showed that all possible relationships of variables were significant at the 0.01 level. The overall research results revealed the existence of significant positive relationships between training and development, job satisfaction, loyalty, and retention.
M. Tech. (Department of Human Resource Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Academics; Higher Education Institutions; Job satisfaction; Loyalty; Retention; Training and development; Dissertations, Academic -- South Africa.; Job satisfaction.; Employee retention.; Employees -- Training of.; Education, Higher -- South Africa.; In-service training.